Artificial Intelligence in Digital Marketing: Descriptive Analysis of Companies' Artificial Intelligence Strategies with Random Sampling - Nihal Toros Ntapiapis (Etkileşim, 2023)
Brands are constantly looking for strategies to meet customer needs in the marketplace and to promote and market their products more effectively. As the new world of technology replaces traditional TV commercials and outdoor billboards, different approaches have emerged. At this point, with the development of computer software and machine learning, Artificial Intelligence (AI) has become an indispensable option for those companies that want to expand their sales and marketing strategies to different dimensions. Artificial Intelligence technologies, deep machine learning and appropriate software can support companies on a wide range of scales, from providing brands with product options suitable for the target audience to offering customers special discounts, or from managing a complete process of collecting marketing data to ensuring that company information is accurately archived in the digital environment. The purpose of this article is to provide a descriptive analysis of the leading companies in today's market, with annual revenues of more than $10 million, that were included in the research through random sampling. At this point, the article draws attention to the importance of AI in the development of brands' marketing strategies and gives several examples of campaigns and applications in which brands have used AI. Finally, as a result of the descriptive analysis, the increase in revenue following the use of AI in marketing strategies and advertising is also considered.